Technology of incubation of goose eggs in the conditions of the Myrgorod private leasing agricultural poultry incubatory-farming enterprise - Ломако, Д. В. (Scientific Progress & Innovations, 2015)
The analysis of influencing of different temperature conditions of incubation of goose eggs is conducted on hatchability and quality of day's youth in the conditions of the Myrgorod poultry incubatory-farming enterprise. It is set that incubation of goose eggs of large size with application of traditional temperature condition of incubation results the decline of their hatchability and qualities of goslings. In this connection there is a necessity to revise the use of the traditional, stable modes of incubation of goose eggs, especially it touches pedigree economies, such as mentioned. As from large sized eggs at the differentiated mode of incubation bigger goslings hatched which better grow and develop and they can be used for repair of herd, as a rule. Thus, in our opinion, it will be contributed in selection work which directed on the increase of meat qualities for the geese of large grey breed. On the whole application of the differentiated temperature condition of incubation enables to promote hatchability of goose eggs on 7–8 percents, and also promotes quality of got day's youth.